Knowledge management for leadership and communication : AI, innovation and the digital economy - Johannessen, Jon-Arild (Emerald points., 2020)
With the establishment of the innovation economy, the Fourth Industrial Revolution is becoming a reality. As this occurs, new forms of leadership arise, generated by the interaction between leadership functions and neurology. From political leadership to organizational structure, these industrial changes will cause ripples throughout our society. It is important to get ahead of these changes, adapting to the new forms of leadership necessary, before these ripples become tidal waves. In order to do so, expert author Jon-Arild Johannessen turns to the processes that are a key part of the innovation economy, examining how value creation is changing in the new Industrial Revolution. In this innovative book, Johannessen asks the question: what are the key value creation processes in the innovation economy? And how do these processes affect the logic of industry and industrial societies?